“Las adaptaciones de música tradicional ecuatoriana para instrumento solista viola y su incidencia en el fortalecimiento de la memoria cultural del Ecuador. Periodo 2018-2019 - Serrano Ochoa, Jorge Andres (2019)
In Ecuador, music developed from European influence and after this cultural miscegenation, manages to obtain its own identity. Thus over the years music together with man began to develop, creating: customs and traditions. The present research is based on the strengthen of cultural memory of Ecuador through the designing of traditional music adaptations focused on the soloist instrument Viola. Project that will be framed in an exploratory type of investigation and will count with the participation of some institutions of musical education in the city of Loja during the period 2018-2019. Through the instruments applied to the main authorities in charge of each musical institution and violists of Loja city, information was collected about the importance of working on a repertory for the instrument Viola parting from the Ecuadorian traditional music, due to the limited access to this repertory that Viola players have. The obtained results, allowed the developing of an alternate proposal that is enclosed in this document, which consists in the compilation, adaptation and arrangements of each one of the selected musical pieces from different traditional music genres in Ecuador, focused to ease the access of the repertory, as well as strengthen the local cultural development; evidencing that way, the importance of doing adaptations of Ecuadorian traditional music for the soloist instrument Viola and encourage future generations to investigate researches of this kind.